THE EFFECT OF FEEDBACK TECHNIQUES AND STUDENTS’ VOCABULARY MASTERY ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE ESSAY - Dwi Suci Amaniarsih (Journal MELT (Medium for English Language Teaching), 2018)
This study was quantitatively conducted to discover whether Feedback Techniques had effect on students’ achievement in writing descriptive essay. By controlling the effect of vocabulary mastery, this study was also conducted to investigate the interaction effect of both independent variables. The population was grade X students of SMA Harapan I Medan 2010-2011 school year. There were eight classes. Each classes consisted of 35 students. Sample of this research was two classes divided into two groups representing the high and low level of vocabulary mastery. The first group was taught by using Peer Response Technique and the second was taught by using Teacher Response Technique. The data collected were analyzed with two ways analysis of variance (2x2 ANOVA). The findings indicated that (1) Peer Response and Teacher Response Techniques significantly affect students’ achievement in writing Descriptive Essay (Sig = 0.013<0.05). Students’ achievement in writing Descriptive taught by using Peer Response Technique is significantly higher than that of students’ taught by using Teacher Response Technique (76.8>74.8), (2) the achievement in writing Descriptive of the students with high vocabulary mastery is significantly higher than that of with low vocabulary mastery (79.8>71) and (3) There is an interaction between feedback techniques and vocabulary mastery to the students’ achievement in writing descriptive (0.002<0.05). Therefore, feedback techniques and students’ vocabulary mastery significantly affect the students’ achievement in writing descriptive. Based on the findings, it is suggested that feedback techniques should be applied in English instruction to develop the students’ writing achievement.